Daddy day care - Davis, John.; Berenson, Matt.; Godfrey, Wyck.; Rodkey, Geoff, 1970-; Carr, Steven (Director); Murphy, Eddie, 1961-; Garlin, Jeff, 1962-; Zahn, Steve, 1968-; King, Regina; Nealon, Kevin, 1953-; Katz, Jonathan, 1946-; Hogan, Siobhan Fallon, 1972-; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2003)
When two fathers find themselves out of work, they decide to start a day care center. When their business starts to take off, the head of a competing prestigious childrens academy tries, with hilarious results, to put them out of business.
Special features: "Meet the 'Daddy day care' kids" featurette; "Quiet on the set!" featurette; "Good morning, Eddie Murphy!" featurette; "What did that kid say?" featurette; name the noise maker game; kid card match up game; odd one out game; blooper reel; all-new animated short "Early bloomers"; theatrical trailer.
Director of photography, Steven Poster ; editor, Christopher Greenbury ; music, David Newman ; costume designer, Ruth Carter ; production designer, Garreth Stover.
Eddie Murphy, Jeff Garlin, Steve Zahn, Regina King, Kevin Nealon, Jonathan Katz, Siobhan Fallon Hogan, Lisa Edelstein, Lacey Chabert, Anjelica Huston.
MPAA rating: PG; for language.
DVD; Dolby digital 5.1, widescreen and full screen versions, NTSC, region 1.
With separate English and French language tracks and English and French subtitles; closed captioned.
Keywords: Day care centers -- Drama; Day care centers -- Employees -- Drama; Father and child -- Drama; Feature films; Comedy films; Films for the hearing impaired